Apple Proliferation Phytoplasma Influences the Pattern of Plant Volatiles Emitted Depending on Pathogen Virulence - Rid, Margit; Mesca, Constanze; Ayasse, Manfred; Gross, Jürgen (Frontiers in Ecology and Evolution, 2016)
Apple proliferation (AP) and pear decline (PD) are the most severe diseases in pome fruit growing areas. AP-infected trees show typical symptoms such as witches’ broom, enlarged stipules, tasteless and dwarf fruits. PD-infected pears show a progressive weakening, reduced terminal growth, smaller fruits and die within weeks (quick decline) or years (slow decline). The diseases are caused by the cell-wall lacking bacteria Candidatus Phytoplasma mali (AP phytoplasma) and Ca. P. pyri (PD phytoplasma), respectively. In previous studies it has been shown that AP-infected apple trees emitted higher amounts of the sesquiterpene β-caryophyllene, an attractant of the insect vector Cacopsylla picta (Hemiptera: Psyllidae), thereby facilitating the dispersal of AP phytoplasma. In the present study, volatile organic compounds (VOCs) occurring in the headspace of plants infected with Ca. P. mali strains causing different severity of symptoms in apple plants were collected, analyzed and identified. Headspace samples from healthy and AP-infected model plant tobacco (Nicotiana occidentalis) and apple (Malus domestica) as well as from healthy and PD-infected pear (Pyrus communis) were investigated via thermodesorption and GC-MS analysis. Significantly higher concentrations of ethyl benzoate were produced in all phytoplasma-infected plants compared to healthy ones and an as yet unidentified sesquiterpene differed between the odor bouquets of healthy and by Ca. P. mali infected tobacco plants. Additionally, statistically significant higher amounts of both compounds were measured in the headspace of plants infected by the virulent AP strain. In apple, significantly higher concentrations of ethyl benzoate and methyl salicylate were observed for trees infected with strains of Ca. P. mali. Ethyl benzoate was also detected in the headspace of pear trees infected with Ca. P. pyri.